Pengaruh Bukaan Pada Ruangan Rumah Type 36 Terhadap Kenyamanan Termal Menurut Persepsi Pengguna - Yeni Bayak Miko; Sri Nengsih; Zia Faizurrahmany El Faridy (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Abstract. A house as a shelter for the occupants requires ventilation, both natural and artificial, to achieve thermal comfort. Openings allow air to circulate in and out of the building, thus affecting the humidity and temperature of the building. The research was located in the Type 36 Mutiara Baet Residence housing complex, in Baet Village, Baitussalam District, Aceh Besar Regency. The case study is a house facing west, east, north, and south which has openings without direct sunlight. Using a mixed method research method, which combines qualitative and quantitative models. Qualitative methods are carried out using documentation, interviews, and observation. while the quantitative method is carried out through measurements of humidity, wind speed, and temperature. Interview results showed that 70% of building occupants said that the residence they lived in felt hot so it was uncomfortable to be indoors without mechanical cooling, while the existing openings could not be maximized for natural ventilation as intended. The remaining 30% of respondents thought that openings could help reduce heat. The results of thermal measurements, the average temperature in the living room was 30.93°C, while the average temperature in the kitchen room was 30.99°C. The results of measuring the average humidity (RH%) in the living room was 46.40% and the average humidity (RH%) in the kitchen room was 46.18%. Only 20% of residential living rooms and kitchens in Mutiara Baet Residence have wind circulation, while in the other 80% of residences, the detected wind speed is 0.0 m/s, which means there is no wind movement/circulation